COHESION OF CONCLUSION IN STUDENT’S ACADEMIC WRITING: CRITICAL DISCOURSE ANALYSIS PERSPECTIVE - Sudar Sudar (University of Kuningan, 2025)
A conclusion of academic writing is an urgent component in writing. Khazaal, (2019), he described that good a conclusion of academic writing has five variables namely; grammar, vocabulary, organizing, content, and cohesion). Based on this idea, researcher would like to limit the discussion on cohesion, organization, and grammar (tenses) conclusion of academic writing written by EFL students. The research questions of this study are as the following; a. What are the cohesive devices written in a conclusion of academic writing? b. how is the organization of conclusion written by EFL students? c. What are the tenses used in the section of conclusion written by EFL students? It is a qualitative descriptive study. The data of this study were twenty-five files of academic writing taken randomly from two classes of forty-five files. To analyse the data researcher used theory of cohesion written by Halliday and Hasan (1976) cited in Jhonson, (2017). Theory of organizing of a conclusion of academic writing by Adizovna, (2023), and the theories of tenses developed by, Bukit and Deli, (2020). The finding of the study revealed that, there were three types of cohesion written by EFL students in writing a conclusion of academic writing namely; grammatical cohesion, reiteration lexical cohesion, and conjunctive adverb to achieve cohesion. Furthermore, there are two types of a conclusion; such as; a conclusion has three components, and a conclusion has two components. Furthermore, there were two types of tenses written in a conclusion of academic writing, namely; simple present and simple past.